Prevalence, molecular signature and risk analysis of tropical theileriosis in Gir cattle in south-western region of Gujarat, India - PARMAR, VIJAY L; VAGH, A A; PATEL, U D; BILWAL, A K; THAKRE, B J; BRAHMBHATT, N N; PATBANDHA, TAPASKUMAR; PARMAR, J N (The Indian Journal of Animal Sciences, 2025)
The study signifies pioneering effort for development of preventive strategies of tropical theileriosis in Gir Cattle by shedding the light on epidemiological information regarding age, season, lactational status, tick infestation and importance of tick control. On the other hand, key clinical observations viz., pyrexia, lymphadenopathy, altered appetite, ocular and nasal discharge, pale mucous membrane, and tick infestations of the study provide the platform for early diagnosis of disease in field conditions to veterinary professionals.